Photoshop CS2 In Simple Steps
The book discusses in detail all its functions and features ranging right from opening a file to basic color manipulation to an image, editing an image, painting, drawing and retouching an image to applying different filters to the graphics to give it different kinds of visual effects such as liquefying, vanishing, artistic, blurring, cutout, neon glow, lens correction, add noise difference clouds and many more.